Step
*
2
of Lemma
locally-non-zero-finite-deriv-seq
1. a : ℝ
2. b : ℝ
3. u : ℝ
4. v : ℝ
5. a ≤ u
6. u < v
7. v ≤ b
8. k : ℤ
9. [%4] : 0 < k
10. ∀f:[a, b] ⟶ℝ
      ((∃F:ℕ(k - 1) + 1 ⟶ [a, b] ⟶ℝ
         (finite-deriv-seq([a, b];k - 1;i,x.F[i;x])
         ∧ (∀x:{x:ℝ| x ∈ [a, b]} . (F[0;x] = f(x)))
         ∧ (∃z:{z:ℝ| z ∈ [u, v]} . (r0 < Σ{|F[i;z]| | 0≤i≤k - 1}))))
      
⇒ (∃z:ℝ. ((u ≤ z) ∧ (z ≤ v) ∧ f(z) ≠ r0)))
11. f : [a, b] ⟶ℝ
12. F : ℕk + 1 ⟶ [a, b] ⟶ℝ
13. finite-deriv-seq([a, b];k;i,x.F[i;x])
14. ∀x:{x:ℝ| x ∈ [a, b]} . (F[0;x] = f(x))
15. z : {z:ℝ| z ∈ [u, v]} 
16. r0 < Σ{|F[i;z]| | 0≤i≤k}
⊢ ∃z:ℝ. ((u ≤ z) ∧ (z ≤ v) ∧ f(z) ≠ r0)
BY
{ TACTIC:(((Assert z ∈ [u, v] BY (DVar `z' THEN Unhide THEN Auto)) THEN RepUR ``i-member`` (-1)⋅)
          THEN (RWO "rsum-split-first" (-2) THENA Auto)
          THEN ((FLemma `radd-positive-implies` [-2] THENM D -1) THENA Auto)) }
1
1. a : ℝ
2. b : ℝ
3. u : ℝ
4. v : ℝ
5. a ≤ u
6. u < v
7. v ≤ b
8. k : ℤ
9. [%4] : 0 < k
10. ∀f:[a, b] ⟶ℝ
      ((∃F:ℕ(k - 1) + 1 ⟶ [a, b] ⟶ℝ
         (finite-deriv-seq([a, b];k - 1;i,x.F[i;x])
         ∧ (∀x:{x:ℝ| x ∈ [a, b]} . (F[0;x] = f(x)))
         ∧ (∃z:{z:ℝ| z ∈ [u, v]} . (r0 < Σ{|F[i;z]| | 0≤i≤k - 1}))))
      
⇒ (∃z:ℝ. ((u ≤ z) ∧ (z ≤ v) ∧ f(z) ≠ r0)))
11. f : [a, b] ⟶ℝ
12. F : ℕk + 1 ⟶ [a, b] ⟶ℝ
13. finite-deriv-seq([a, b];k;i,x.F[i;x])
14. ∀x:{x:ℝ| x ∈ [a, b]} . (F[0;x] = f(x))
15. z : {z:ℝ| z ∈ [u, v]} 
16. r0 < (|F[0;z]| + Σ{|F[i;z]| | 0 + 1≤i≤k})
17. (u ≤ z) ∧ (z ≤ v)
18. r0 < |F[0;z]|
⊢ ∃z:ℝ. ((u ≤ z) ∧ (z ≤ v) ∧ f(z) ≠ r0)
2
1. a : ℝ
2. b : ℝ
3. u : ℝ
4. v : ℝ
5. a ≤ u
6. u < v
7. v ≤ b
8. k : ℤ
9. [%4] : 0 < k
10. ∀f:[a, b] ⟶ℝ
      ((∃F:ℕ(k - 1) + 1 ⟶ [a, b] ⟶ℝ
         (finite-deriv-seq([a, b];k - 1;i,x.F[i;x])
         ∧ (∀x:{x:ℝ| x ∈ [a, b]} . (F[0;x] = f(x)))
         ∧ (∃z:{z:ℝ| z ∈ [u, v]} . (r0 < Σ{|F[i;z]| | 0≤i≤k - 1}))))
      
⇒ (∃z:ℝ. ((u ≤ z) ∧ (z ≤ v) ∧ f(z) ≠ r0)))
11. f : [a, b] ⟶ℝ
12. F : ℕk + 1 ⟶ [a, b] ⟶ℝ
13. finite-deriv-seq([a, b];k;i,x.F[i;x])
14. ∀x:{x:ℝ| x ∈ [a, b]} . (F[0;x] = f(x))
15. z : {z:ℝ| z ∈ [u, v]} 
16. r0 < (|F[0;z]| + Σ{|F[i;z]| | 0 + 1≤i≤k})
17. (u ≤ z) ∧ (z ≤ v)
18. r0 < Σ{|F[i;z]| | 0 + 1≤i≤k}
⊢ ∃z:ℝ. ((u ≤ z) ∧ (z ≤ v) ∧ f(z) ≠ r0)
Latex:
Latex:
1.  a  :  \mBbbR{}
2.  b  :  \mBbbR{}
3.  u  :  \mBbbR{}
4.  v  :  \mBbbR{}
5.  a  \mleq{}  u
6.  u  <  v
7.  v  \mleq{}  b
8.  k  :  \mBbbZ{}
9.  [\%4]  :  0  <  k
10.  \mforall{}f:[a,  b]  {}\mrightarrow{}\mBbbR{}
            ((\mexists{}F:\mBbbN{}(k  -  1)  +  1  {}\mrightarrow{}  [a,  b]  {}\mrightarrow{}\mBbbR{}
                  (finite-deriv-seq([a,  b];k  -  1;i,x.F[i;x])
                  \mwedge{}  (\mforall{}x:\{x:\mBbbR{}|  x  \mmember{}  [a,  b]\}  .  (F[0;x]  =  f(x)))
                  \mwedge{}  (\mexists{}z:\{z:\mBbbR{}|  z  \mmember{}  [u,  v]\}  .  (r0  <  \mSigma{}\{|F[i;z]|  |  0\mleq{}i\mleq{}k  -  1\}))))
            {}\mRightarrow{}  (\mexists{}z:\mBbbR{}.  ((u  \mleq{}  z)  \mwedge{}  (z  \mleq{}  v)  \mwedge{}  f(z)  \mneq{}  r0)))
11.  f  :  [a,  b]  {}\mrightarrow{}\mBbbR{}
12.  F  :  \mBbbN{}k  +  1  {}\mrightarrow{}  [a,  b]  {}\mrightarrow{}\mBbbR{}
13.  finite-deriv-seq([a,  b];k;i,x.F[i;x])
14.  \mforall{}x:\{x:\mBbbR{}|  x  \mmember{}  [a,  b]\}  .  (F[0;x]  =  f(x))
15.  z  :  \{z:\mBbbR{}|  z  \mmember{}  [u,  v]\} 
16.  r0  <  \mSigma{}\{|F[i;z]|  |  0\mleq{}i\mleq{}k\}
\mvdash{}  \mexists{}z:\mBbbR{}.  ((u  \mleq{}  z)  \mwedge{}  (z  \mleq{}  v)  \mwedge{}  f(z)  \mneq{}  r0)
By
Latex:
TACTIC:(((Assert  z  \mmember{}  [u,  v]  BY  (DVar  `z'  THEN  Unhide  THEN  Auto))  THEN  RepUR  ``i-member``  (-1)\mcdot{})
                THEN  (RWO  "rsum-split-first"  (-2)  THENA  Auto)
                THEN  ((FLemma  `radd-positive-implies`  [-2]  THENM  D  -1)  THENA  Auto))
Home
Index